Propriedades medicinais de células-tronco amnióticas - de Carvalho, Braulio Fernandes; Sousa, Deny Berg de Carvalho; Neto, Aloísio José Portela; Nunes, João Paulo Silva; de Vasconcelos, Paula Andrea Sampaio [UNESP] (My University, 2013)
The current regenerative medicine is still incapable of creating full organs in vitro. Transplantation queues are a worrying problem in most of countries, without an apparent coming solution. The research with several types of stem cells has shown that the use of cells to repair damaged organ can be as effective as replacing the whole organ. Particularly, stem cells populations from the amniotic sac possess properties beyond the physical constitution and are capable of secreting cytokines with anti-inflammatory action and growth factors with potential to mobilize stem cells from the own body. Transplantation of amniotic stem cells can be an alternative to optimize surgical procedures, to increase organ and stem cells transplantation success rate, to help in the treatment of several diseases and to accelerate patient's recovery.
Medicinal properties of amniotic stem cells
Keywords: Adult stem cells; Amnion; Cytokine; Inflammation; Organ transplantation